2008
DOI: 10.1021/pr800226w
|View full text |Cite
|
Sign up to set email alerts
|

A Spectral Clustering Approach to MS/MS Identification of Post-Translational Modifications

Abstract: Unidentified tandem mass spectra typically represent 50-90% of the spectra acquired in proteomics studies. This manuscript describes a novel algorithm, "Bonanza", for clustering spectra without knowledge of peptide or protein identifications. Further analysis leverages existing peptide identifications to infer related, likely valid identifications. Significantly more spectra can be identified with this approach, including spectra with unexpected potential modifications or amino-acid substitutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 26 publications
0
69
0
4
Order By: Relevance
“…We also, for the first time, proposed the FDR estimation of propagating annotations through a spectral network. Although some approaches have proposed the identification of modified peptides by propagating annotations (3941), none has fully addressed FDR estimation. Our approach ensures a conservative estimate of the FDR and is increasingly rigorous for higher-modified peptides.…”
Section: Discussionmentioning
confidence: 99%
“…We also, for the first time, proposed the FDR estimation of propagating annotations through a spectral network. Although some approaches have proposed the identification of modified peptides by propagating annotations (3941), none has fully addressed FDR estimation. Our approach ensures a conservative estimate of the FDR and is increasingly rigorous for higher-modified peptides.…”
Section: Discussionmentioning
confidence: 99%
“…These spectral pairs are then constructed into networks of related spectra, from which more informative virtual spectra can be generated to facilitate de novo peptide sequencing, and also unanticipated modifications can be identified by propagation of database search results. Similarly, the Bonanza algorithm of Falkner et al (44) uses an improved version of the common spectral-dot-product similarity with shifted mass matching window to cluster related spectral pairs. Ahrne et al (45) proposed to construct an online library of spectra confidently identified by sequence database search and subsequently search the remaining unidentified spectra against the spectral library with a very large precursor mass tolerance.…”
Section: Liquid Chromatography Coupled With Tandem Mass Spectrometrymentioning
confidence: 99%
“…When assessing the similarity of spectra, spectral clustering can be performed 53, 54, 55, 56. While transitive identifications and consensus or representative spectra have been reported in all of these studies, the concept was further developed in the creation of spectral archives 57.…”
Section: Introductionmentioning
confidence: 99%